Analysis of risk factors for poor prognosis after endovascular treatment of tandem lesions in acute ischemic stroke - Zhang, Yifan; Zhou, Xinmin; Cao, Cheng; Huang, Xin (Frontiers in Neurology, 2025)
Aims/backgroundIn China, the incidence of acute ischemic stroke (AIS) has been rising annually, accounting for 60–70% of all stroke cases. To explore the risk factors leading to poor prognosis after endovascular treatment in patients with acute ischemic stroke tandem lesions after endovascular treatment.MethodsA retrospective analysis was conducted on the clinical data of patients with tandem lesions who underwent endovascular therapy at Jiangyin People’s Hospital affiliated with Xuzhou Medical University, from July 2018 to August 2023. Post-treatment revascularization was assessed using the modified Thrombolysis in Cerebral Infarction (mTICI) grading system, with grades 3 and 2b indicating good recanalization and grades 2a and below indicating poor recanalization. Patient prognosis at 90 days post-procedure was evaluated using the modified Rankin Scale (mRS), with scores of 0–2 classified as good prognosis and 3–6 as poor prognosis. The age, admission National Institutes of Health Stroke Scale score (NIHSS), gender, hypertension, diabetes mellitus, coronary artery disease, smoking, atrial fibrillation, carotid artery stenting, revascularization, site of tandem lesion (anterior or posterior circulation), and onset-recanalization time (minutes) of the enrolled patients were subjected to univariate analysis. Univariate analysis was performed, followed by multivariate logistic regression for variables with p < 0.1.ResultsA total of 75 patients were included, of whom 32 had good 90-day outcomes and 43 had poor outcomes. Compared to the good outcome group, patients with poor outcomes were older, had higher NIHSS scores at admission, and were less likely to achieve good recanalization (all p < 0.05). Multivariate analysis identified older age, higher NIHSS score, and poor recanalization as independent predictors of poor prognosis. The area under the ROC curve for the NIHSS score was 0.735 (p = 0.001), indicating moderate predictive value.ConclusionAdvanced age, elevated NIHSS score on admission, and suboptimal recanalization are independently associated with poor 90-day outcomes following endovascular treatment for tandem lesions. The NIHSS score may aid in early risk stratification.